PENGEMBANGAN MANAJEMEN LEMBAGA PENDIDIKAN ISLAM BERBASIS MERDEKA BELAJAR - Novri Agus Parta Wijaya; Zulfani Sesmiarni; Darul Ilmi; Supratman Zakir; Ali Mustopa Yakub Simbolon; Ezi Mulia (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2023)
The purpose of this article is to explain in simple terms the concept of independent learning offered by the Minister of Education, Culture, Research and Technology and Higher Education (Menristekdikti) and its implementation in Islamic educational institutions. Free Learning Education is a response to the needs of the education system in the Industrial Revolution 4.0 era. In the era of the Industrial Revolution 4.0, the main need to be achieved in the education system or more specifically in learning methods, namely students or students, is mastery of new literacy. The new literacy is First, data literacy. Second, technological literacy. Finally, human literacy. In addition, the Free Learning Education system also prioritizes character education. This article uses library research. With data sources from journals, research reports, scientific magazines, newspapers, relevant books, results of seminars, unpublished scientific articles, sources, bibliographical letters, and so on. So in this study, learning methods in the era of the Industrial Revolution 4.0 can determine the success of learning because one of the characteristics of the concept of education 4.0 is the position of students as educational subjects (student centered), integration of material and teaching and learning processes (PBM) with the demands of modern knowledge, society and the world of work. And the methods used vary, but in the independent education system learning the Blended Learning method is ideal as a learning method.